Management Model for Successful Business Processes: the Case of Transition Countries - Gošnik, Dušan; Beker, Ivan; Suklan, Jana; Kavčič, Klemen (International Journal of Industrial Engineering and Management, 2016)
The paper presents the results of empirical research about the effect of management activities such as planning, organising, leading and controlling on the success of business processes` improvement performance. We report the results of a survey conducted in various types of organisations in transition economies. Results show us important differences about how certain management activities affect the success of business processes` improvement implementation. The findings are useful for business practice in general and for managers in countries having a similar history, social system background and transition economy (e.g. Serbia, Slovenia, etc.) as they will understand better the key influences and the role of management activities in business processes improvement initiatives and implementation. Article history: Received (18.02 2016.); Revised (10.05.2016.); Accepted (20.05.2016.)